Future Demographic Challenges in the Arab World - Goujon, Anne.; Barakat, Bilal (Abu Dhabi : Emirates Center for Strategic Studies and Research, 2010)
"Our perspective will first of all examine the differences in terms of demographic paths existing in the 22 countries that make up the Arab world, as well as any convergence occurring at different levels. While the notion that there is a unique and unchanging demographic pattern that is specifically Arab - one of universally high fertility that does not decline - is no longer tenable, the countries in the region are sufficiently similar to each other and distinct from their neighbors to be meaningfully discussed together. This is not to lose sight of the fact that modernity, cultural openness, the relations between men and women, the effects of economic crisis and of development all vary from one sub-population to another, in North Africa and the Middle East, as elsewhere in the world. ... For this purpose, the region has been divided into four major sub-groups: Arab Least Developed Countries (LDCs), member states of the Gulf Cooperation Council (GCC), North African countries and Eastern Mediterranean countries in the broad sense including Jordan and Iraq (the Mashreg)". -- p.1-2.
Includes bibliographical references (pages 67-72).
Keywords: Demography -- Research -- Arab countries; Demographic surveys -- Arab countries; Arab countries -- Population -- 21st century